A metaformulação no discurso didático - Souza, Sílvia Fernanda (2007)
This work is placed in the scope of the studies of the spoken language and has as object the text spoken in the classroom, conceived as an interaction product between the interlocutors in a face to face situation. We have joined to the works that try to describe and, consequently, understand the procedures of constitution of the spoken text, whether they are of verbalization (construction), treatment (reformulation) or discursive qualification (metadiscursive), so we intend to focus the meta-formulative procedures and its contributions for the didactic situations. Such didactic situations, for its asymmetrical character, may be spaces in which they show meta-formulative strategies in the teacher speech to keep the attention of the listener, to ensure his/her understanding or even to show his/her domain of the culture norm. Bearing in mind these assumptions, the objective of this research is to identify and to describe how the meta-formulation procedures - that exist in the construction of the spoken text by teachers occur, describing the found meta-formulative procedures pointing out the formal and functional strategies and characteristics for the monitoring of the speech, as well as the procedures found in didactic situations of exposition with different symmetries. Two didactic situations have been analyzed: where the teacher speech dominates the turn (Formal Elocution) and where there are verbal interventions, with alternation of turns among the teacher and the students (expositive and dialogue lesson). The analysis of the metaformulative activities was accomplished by the joining in distinct categories, whose functions have been described. It was realized that in both didactic expositions there is the presence of the dialogue, which is present in the addressing of the text of the teacher. In the Formal Elocution the teacher uses strategies of reformulation, specially paraphrases and repetitions that try to clarify terms and keep the attention of the interlocutor. In this situation there have been few meta-discursive manifestations. Also, some strategies of enunciation have been noticed in order to provoke involvement of the interlocutors. Otherwise, in the expositive and dialogued Lesson because of the alternation of turns, there are several situations that the procedures of construction and reformulation are shared among teacher and students and the strategies assume different functions because the teacher has a feedback through the verbal interaction of the students